Lessons from overtly-headed exclamatives in Spanish varieties: Implications for the account of obligatory subject-verb inversion - Villa-García, Julio (Isogloss, 2024)
Inverting wh-exclamative sentences with an overt complementizer in languages like Spanish pose a serious challenge to traditional accounts of obligatory subject-verb inversion. Such analyses assume either T-to-C movement or Spec,TP as an A-bar position capable of hosting wh-phrases and subjects alike. The optional presence of a complementizer in the head of CP in exclamatives prevents the verb from moving to CP, which argues against an analysis of inversion wherein the verb moves to Cº. Regarding the Spec,TP-as-an-A-bar-position account, if the wh-phrase sits in Spec,TP and competes with the subject for that position, the presence of a complementizer below wh-phrases in exclamatives is then rather mysterious, since que ‘that’ is standardly assumed to signal the presence of CP structure –not IP/TP structure. However, for those cases in which the complementizer occurs, a combined approach consisting of a modification of the Spec,TP-as-an-A-bar-position account which assumes further movement of the exclamative wh-phrase to a CP-related/left-peripheral projection headed by the complementizer is shown to be empirically superior to the competing proposals on the market. Furthermore, dialect data show that the presence of que is sensitive to the type of exclamative phrase in its specifier. The inverting exclamative data with overt que also indicate that it is the full projection consisting of the exclamative wh-phrase in the specifier plus the overt complementizer  in the head that needs to be adjacent to the verb in such environments.